Motivasi Kerja Pustakawan Berdasarkan Teori Hirarki Kebutuhan Abraham Maslow - Triningsih; Masruri, Anis; Premierita Haryanti, Ni Putu (Media Informasi, 2025)
Librarian work motivation is very important to improve service quality. This study aims to analyze the work motivation of librarians at the Bank Indonesia Solo Library using Abraham Maslow's Hierarchy of Needs Theory. This research is a field research, which uses data collection techniques in the form of documentation and interviews. The informants of this research are librarians of Bank Indonesia Solo Branch. Data analysis uses Abraham Maslow's Hierarchy of Needs Theory. The results showed that librarians' work motivation is influenced by the fulfillment of basic needs, namely adequate salaries; security needs, namely a comfortable work environment; social needs, namely the LENTERA (Learning Literacy on Friday) program, news summaries, and e-cliping; appreciation needs, namely the Bank Indonesia Library Librarian Communication Forum event which gives awards to the most active librarians and accredited libraries; and self-actualization needs, namely online seminars from the National Library and Bank Indonesia Headquarters, and the “Limas Nusantara” program which contains daily library programs. Keywords: Work Motivation; Librarian; Maslow's Hierarchy of Needs; Bank Indonesia Solo Library; Job